From board diversity to disclosure: A comprehensive review on board dynamics and ESG reporting - Sheela Sundarasen; Rajespari Kumar; Krishna Tanaraj; Ahnaf Ali Al-smady; Usha Rajagopalan (Research in Globalization, 2024)
This study aims to provide a comprehensive overview of scholarly work and discussion on board diversity and ESG reporting, leading to the identification of prominent themes and potential future research. Based on 144 articles from the Web of Science (WoS) database, the study adopts numerical and visualization techniques using the Vosviewer and Biblioshiny R-package to examine the extant literature from 2011 to 2023. The outcomes of the scientific bibliographic coupling identified three dominant themes: Theme 1, 'Board Gender Diversity and Sustainability Reporting'; Theme 2, 'Importance of Governance Structures in shaping reporting practices' and Theme 3, 'Factors Shaping Integrated Reporting'. The review concludes that board diversity supports environmental, social, and governance reporting and proves integral to sustainable corporate practices and contextspecific strategies. Policymakers should design inclusive governance frameworks by recognizing the role of board diversity in enhancing ESG reporting quality, leading to regulatory reforms that encourage greater gender diversity and transparency in sustainability practices. As for businesses, having diverse boards enhances decision making and innovation, improving ESG reporting quality and fostering better sustainability outcomes. Finally, for academia, the research provides a foundation for future studies on the intersection of board diversity and ESG reporting, particularly in exploring cultural and regional variations, as well as the role of technology in improving disclosure quality. Thus, this study is expected to have far-reaching implications for policymaking, business strategies, societal decisions, and academic research, which could eventually contribute to quality sustainability reporting and business sustainability.
Keywords: 330; Board diversity; Gender diversity; ESG reporting; Sustainability reporting; Integrated reporting; Bibliometric analysis